Le DCP dérivant pour et par l’arène thonière tropicale - Nastassia Reyes; Manon Airaud (Revue d'anthropologie des connaissances)
Used as one of the preferred means of accessing a large volume of fish, drifting Fish Aggregating Devices (dFAD), floating and drifting structures under which fish are aggregated, geo-tracked at a long distance and deployed in high seas by the fisherman, are now central in debates on the future of the French industrial tuna fishery. With the objective of contributing to a better understanding of these debates around dFADs, this article proposes to describe these objects in their socio-technical dimension, i.e., their material and technical dimensions, but also the plural relationships that they maintain with their biophysical and human environment. It first traces the multiple lives of a dFAD, from its manufacture on the docks of the fishing port of Abidjan to the knowledge it produces. It addresses the modes of regulation of dFADs and the way in which they are embedded in multiple representations. The dFAD is presented as a case study of an object that makes technology an eminently social construct, and whose status changes according to economic, social, political, environmental or legal events and circumstances. Based on ethnographies conducted in different sites (from fishing ports to decision-making bodies), this contribution focuses on the plural representations of the actors of the French tropical tuna industry (scientists, spokespersons of the fisheries sector, fishermen, representatives of environmental NGOs, national civil servants) that influence the regulatory mechanisms of drifting FADs.